Does Prison Deter Drunk-Drivers? - Rahman, Sara (Journal of quantitative criminology, 2021)
Objective To examine the specific deterrent effect of prison on driving under the influence of alcohol (DUI) recidivism. Method The study outcomes were the probabilities of DUI re-offending over 6 months, 24 months and 5 years ‘free time’ (i.e. time not spent in custody). The comparison group consisted of offenders convicted of DUI offending who received a suspended sentence of imprisonment. The effect of imprisonment was examined in a series of 2SLS models; employing an extensive set of controls (age, gender, race, remoteness of residence, socioeconomic status, legal representation, number of concurrent offences, DUI blood alcohol range, number of prior court appearances, prior penalties) and variation in the judicial proclivity to imprison convicted drunk drive offenders as an instrument to identify the effect of prison on DUI re-offending. Results Our free-time analyses reveal no evidence that imprisonment reduces the risk of DUI recidivism. Separate analyses for first-time DUI offenders revealed a slight (5%) reduction in re-offending over 24 months free time but no effect over 5 years. Conclusion We conclude that the funds currently spent on imprisoning DUI offenders could be more fruitfully be invested in measures that show more promise in reducing DUI recidivism.